Evaluation of the Antibacterial Effectiveness of Cinnamon (Cinnamomum burmanii) Infusion Against Staphylococcus aureus: Uji Efektivitas Infusa Kayu Manis (Cinnamomum Burmanii) Sebagai Antibakteri Staphylococcus Aureus - Ekasinta, Meilisa; -, SASTRA GANDHI ARAB (Infomasi dan Promosi Kesehatan, 2025)
Some bacteria have been reported to be resistant to several antibiotics due to irrational use, and this resistance can make infections caused by Staphylococcus aureus difficult to treat. Therefore, new antibiotics are needed to treat infections caused by resistant bacteria. This study was conducted to test the effectiveness of cinnamon infusion as an antibacterial agent against Staphylococcus aureus. The type of research was experimental, using a Posttest Only Control Group Design. The antibacterial effectiveness test of Staphylococcus aureus used cinnamon infusion as the test sample, with zone of inhibition diameter testing through the agar diffusion method, using chloramphenicol as a positive control, sterile NaCl as a negative control, and Minimum Inhibitory Concentration (MIC) with the liquid dilution method as well as Minimum Bactericidal Concentration (MBC) using the disk (well) method. The results of the cinnamon infusion effectiveness test showed that the zone of inhibition diameter against Staphylococcus aureus at a concentration of 50% was 20.36 mm. The Minimum Inhibitory Concentration of cinnamon infusion (Cinnamomum burmanii) against Staphylococcus aureus at a concentration of 10% showed clarity after being incubated for 24 hours at 37°C. The Minimum Bactericidal Concentration test of cinnamon infusion at concentrations of 10%-50% was not able to kill Staphylococcus aureus. Based on this study, cinnamon infusion (Cinnamomum burmanii) is effective in inhibiting Staphylococcus aureus but has not been able to kill the test bacteria.